Melting Dr. Grumpy's frozen heart - Wilson, Scarlet (Harlequin medical romance., 2024)
After his engagement to another doctor collapsed, oncologist Jay has had it with hospital relationships. But something about new colleague Dr. Skye and her Miss Sunshine personality intrigues him… Skye needs Jay to sign off on the groundbreaking cancer research that has been her solace since her own devastating loss. She can’t resist tempting this grumpy doc out of his shell with some festive treats, but it’s their chemistry that sparkles like fairy lights! Can Skye melt Jay’s frosty facade for a chance at happy-ever-after?